(untitled) (PerCursos, 2022)
This paper seeks to reflect about the implementation of the North American fast food restaurant chain Kentucky Fried Chicken (KFC), specialized in selling fried chicken in buckets, in Belo Horizonte (MG). Simultaneously, it analyzes the development of Brazilian chains and stores which mimic the KCF concept, having the two circuits of the urban economy, proposed by Milton Santos as a theory basis (SANTOS, 1979). This businesses in town, comply with the existence of imitations (related to the inferior or marginal superior circuits) which preceded the very presence of the “original” (representative of the superior circuit). Thus, the space reveals locations and tasks that differentiate themselves in capital, technology, and organization degrees. In this dialectic relation, it was noted that the national/regional franchises, local businesses, and KFC affiliates coexist, generating new spacial organizations, according to each social context in place and hosting overlays of social and territorial division of labor and interdependent acting agents. The research has relied on semi structured interviews and field studies held in KCF units, in Brazilian franchises and local businesses which sell fried chicken buckets in the city of Belo Horizonte (MG).